The Goldilocks Effect in Infant Auditory Attention. Issue 5 (3rd July 2014) - Kidd, Celeste; Piantadosi, Steven T.; Aslin, Richard N.
<x xml:space="preserve">Abstract</x> Infants must learn about many cognitive domains (e.g., language, music) from auditory statistics, yet capacity limits on their cognitive resources restrict the quantity that they can encode. Previous research has established that infants can attend to only a subset of available acoustic input. Yet few previous studies have directly examined infant auditory attention, and none have directly tested theorized mechanisms of attentional selection based on stimulus complexity. This work utilizes model‐based behavioral methods that were recently developed to examine visual attention in infants (e.g., Kidd, Piantadosi, & Aslin, 2012). The present results demonstrate that 7‐ to 8‐month‐old infants selectively attend to nonsocial auditory stimuli that are intermediately predictable/complex with respect to their current implicit beliefs and expectations. These findings provide evidence of a broad principle of infant attention across modalities and suggest that sound‐to‐sound transitional statistics heavily influence the allocation of auditory attention in human infants.